Scientific dissemination, duty or responsibility?: Assessment of University of Costa Rica academic staff - Castillo Vargas, Andrés (2018)
This article is aimed at knowing the attitude of researchers at University of Costa Rica (UCR) regarding scientific dissemination. For this purpose, the Theory of Reasoned Action (TAR) was used with the purpose of building a model based on structural equation modeling that would allow the identification of the factors that facilitated the staff ’s intentions to disseminate information. In terms of methodology, researchers working in 25 UCR research centers and institutes in the areas of Basic Sciences and Social Sciences were surveyed using an electronic questionnaire. According to the main findings, overestimation of dissemination is identified within the university merit system, especially activities such as writing scientific papers. Furthermore, the factors that facilitated the subjects’ intent to participate in outreach activities are mainly related to the attitude and behavioral control perceived. Finally, based on the analytical approach used, it is imperative for academic communities to have new referential frameworks that would provide a broader view of the scientific communication processes that they can use to challenge and change their positions regarding the traditional assessment they have regarding dissemination.